PANDANGAN PETANI TERHADAP KONSEP PHT DALAM MENGENDALIKAN Spodoptera frugiperda PADA TANAMAN JAGUNG DI DESA KUTA TENGAH, KABUPATEN DELI SERDANG - Nurhajijah Nurhajijah; Hadriman Khair; Wahyuni Umami Harahap; Wizni Fadhillah; Hazen Arrazie Kurniawan; Riris Nadia Syafrilia Gurning (Agros Journal of Agriculture Science, 2023)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is an invasive pest that attacks maize plants. Meanwhile, one of the food crop needs that must be fulfilled is corn. Central Kuta Village is one of the corn-producing villages. In the cultivation of corn, the pest Spodoptera frugiperda is one of the problems that causes up to 50% damage. in the management of Spodoptera frugiperda attacks, many farmers use chemical pesticides. the use of high chemical pesticides can damage the ecosystem. To maintain the balance of the ecosystem, it is necessary to apply integrated pest management (IPM) in corn cultivation. The research was carried out in June 2023 on maize farmers' land in Di Desa, Central Kuta, Namorambe District, Deli Serdang Regency which covered 5 locations from Central Kuta Village. Data was collected through interviews with a questionnaire guide. The data collected were the understanding and perception of IPM of Spodoptera frugiperda on maize plants and the intensity of Spodoptera frugiperda attacks. From the results of the study that out of 5 lands only 4 lands implemented IPM. The intensity of Spodoptera frugiperda attacks on land 4 was the lowest intensity. Based on the results of interviews with 4 farmers, they applied IPM both before planting and until they did not control plant-disturbing organisms.INTISARISpodoptera frugiperda (Lepidoptera: Noctuidae) merupakan hama invasive yang menyerang tanaman jagung.  Sedangkan, salah satu kebutuhan tanaman pangan yang harus dipenuhi adalah jagung. Desa kuta tengah merupakan salah satu desa penghasil jagung. Dalam budidaya tanaman jagung hama Spodoptera frugiperda menjadi salah satu masalah yang mengakibatkan kerusakan mencapai 50%. Dalam pengelolaan serangan Spodoptera frugiperda petani banyak menggunakan pestisida kimia. Penggunaan pestisida kimia yang tinggi dapat merusak ekosistem. Untuk menjaga keseimbangan ekosistem maka perlu diterapkan pengelolaan hama terpadu (PHT) dalam budidaya tanamn jagung. Penelitian   dilaksanakan   pada   bulan juni  2023  pada  lahan  petani jagung di Di Desa, Kuta Tengah, Kecamatan Namorambe Kabupaten, Deli Serdang yang  meliputi 5  lokasi dari desa kuta tengah. Data dikumpulkan melalui wawancara dengan panduan kuesioner. Data yang dikumpulkan yaitu pemahaman dan  persepsi PHT Spodoptera frugiperda tanaman jagung serta intensitas serangan Spodoptera frugiperda.  Dari hasil penelitian bahwa dari 5 lahan hanya 1 lahan yang menerapkan PHT. Intensitas serangan Spodoptera frugiperda pada lokasi 4 merupakan intensitas yang paling rendah. Berdasarkan hasil wawancara petani lokasi 4 menerapkan PHT baik dari sebelum tanam dan sampai tindak pengendalian organisme pengganggu tanaman.